An analysis of respiratory syncytial virus infections in children up to 24 months old hospitalised in the Department of Paediatrics, Paediatric Nephrology and Allergology of the Military Institute of Medicine between 2016 and 2017 - Karolina Cegielska; Milena Pogonowska; Bolesław Kalicki (Pediatria i Medycyna Rodzinna, 2018)
Respiratory syncytial virus (RSV) is the most common pathogen causing bronchiolitis and pneumonia in children up to 24 months old. The virus infects 90% of children within the first 2 years of life, with the highest infection rates in children aged between 6 weeks and 6 months. The majority of cases occur in winter (January and February). Although RSV infection is usually mild, only 1% of children are asymptomatic. All levels of the respiratory system may be affected. Usually mild upper respiratory infections not requiring hospitalisation are observed. About 10% of infected children develop bronchiolitis. RSV infection is the cause of 17–20% of all infantile hospitalisations. Long-term studies have demonstrated a relationship between RSV and obstructive ventilatory disorders in the first decade of life. However, no clear cause and effect relationship was found in this case. It is supposed that RSV infection may only reveal the genetic predisposition to this type of response in children. The aim of the study was to analyse the course of RSV infection in a group of 71 children up to 24 months old. Attention was paid to risk factors, patient’s age, gender distribution in the study group, the number of cases in each month, laboratory and imaging findings as well as family and individual history of atopy. We also discussed the use of inhaled medications, the need for extended diagnosis and accessory testing during infection.